Learning Analytics in Higher Education: A Reflection - John Zilvinskis; James E. Wills, III (Park University, 2019)
The idea of learning analytics has become popularized within higher education, yet many educators are uncertain about what is entailed when implementing these technologies into practice. The following article serves as an overview to the field of learning analytics for faculty, educators for whom the expectations to use these technologies continues to increase. We additionally argue that those who work directly with students need a functional understanding of the learning analytics landscape in order to exercise their own expertise.